Storage stability of vacuum-packaged hotsmoked Rainbow trout (Oncorhynchus mykiss) fillets: color and texture aspects - ELEFTHERIADOU (Α. ΕΛΕΥΘΕΡΙΑΔΟΥ), A.; VARELTZIS (Κ. ΒΑΡΕΛΤΖΗΣ), K.; AMVROSIADIS (,1. ΑΜΒΡΟΣΙΑΔΗΣ), I.; GEORGAKIS (ΣΠ. ΓΕΩΡΓΑΚΗΣ), S. (Journal of the Hellenic Veterinary Medical Society, 2018)
The aim of this research was to investigate some problems related to Rainbow trout's (Oncorhynchus mykiss) hot-smoking process as well as the color texture evaluation of the final product. The skin-on and skin-off fillets were hot-smoked and kept in vacuum-packed storage at 2°C±0.1. Color and texture measurements and biochemical analysis were carried out during 120 days of storage on days 1, 45, 75 and 120. The results have showed no significant differences between skin-on and ski-off fillets in carotenoids and retinol content. This values were reduced from 0,4-0,5 and 0,08-0,10 mg/g (1st day) to 0,2 and 0,04 mg/g by day 45 respectively. Thereafter they remained unchanged until the end of the storage. However, they were proved sufficient for the stability of the red color of the final product, as the a* value remained fairly constant, during the whole storage period. Significant differences between skin-on and skin-off fillets were observed in their external surface color. Both L* and a* values were lower in skin-off fillets and this is probably attributed to the more intense dehydration and absorption of the smoke constituents in this fillets. Moreover, the filleting of raw material before processing, resulted in both complete absence of fish gapping in the end product and satisfactory texture, which remained the same during the whole storage period.